English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

We are doing factoring in school by "completing squares", and I'm having problems with these two equations.

The square root of (x-3)² = the square root of 3

The square root of (x+6)² = the square root of 33

2007-01-18 10:44:48 · 1 answers · asked by cowboysblow27 3 in Science & Mathematics Mathematics

1 answers

Take the square root of both sides
x-3 = +/- sqrt(sqrt(3))
x=3+/- sqrt(sqrt(3))
= 3+/- fourthroot(3)

The other one is similar.

2007-01-18 10:49:40 · answer #1 · answered by Professor Maddie 4 · 1 0

fedest.com, questions and answers